Cycle closure of nutrients and power generation potential by anaerobic treatment of sewage: case study in Las Juntas de Abangares, Costa Rica - Solano Ramírez, Viviana (2022)
[Introduction]: An adequate selection of technology in wastewater treatment plants (WWTPs) and the search for solutions to integrate these systems in the communities are necessary to promote a sustainable sanitation in the Latin American region. [Objective]: This article evaluates the recovery potential of by-products in an anaerobic-based WWTP for the community of Las Juntas de Abangares (10 000 inhabitants). [Methodology]: A mathematical model of mass and energy balance in the community was formulated to estimate the nutrient fluxes (N, P, K) and biogas generation in a proposed WWTP for the population, with an anaerobic reactor as treatment technology. The potential of use of nutrients (liquid and solid phase) to substitute chemical fertilizers in the Abangares region was evaluated and different energy uses of biogas were compared. [Results]: The results show that all the nutrients can be used in Abangares, as this supply would represent less than 1 % of the total demand of the grassland area available in this area. Additionally, the potential savings derived from the use of nutrients and biogas amounted to US $ 50 and 30 thousand dollars per year, respectively, and the use of biogas to replace firewood or cooking gas would allow a negative carbon WWTP. [Conclusions]: The study shows the potential of anaerobic reactors to promote a sustainable sanitation in the region, generating direct benefits and allowing a better integration of the treatment systems in the communities of Costa Rica and other Latin American countries.